ХАРАКТЕР ЕКСПРЕСІЇ ГЕНІВ MMP2 AND MMP9 У ТКАНИНІ РАКУ МОЛОЧНОЇ ЗАЛОЗИ РОЗРІЗНЯЄТЬСЯ У ХВОРИХ РІЗНИХ ВІКОВИХ ГРУП - Lukianova, N.; Mushii, O.; Borikun, T.; Zadvornyi, T.; Bazas, V.; Krotevych, M.; Sivak, L.; Lyalkin, S.; Martynyuk, О.; Hrybach, S.; Chekhun, V. (PH Akademperiodyka, 2023)
Background: Despite the large number of studies devoted to the study of the features of tumor microenvironment in breast cancer (BCa), presently there is no consensus on the features of MMP-2 and MMP-9 expression in the tumor tissue of BCa patients depending on the age. The aim of the study was to investigate the relationship between MMP-2 and -9 expression at the protein and mRNA levels in BCa tissues and the clinical and pathological features of BCapatientsin different age groups. Materials and Methods: The expression level of MMP-2 and -9in the BCa tissue of patients of two age groups (< 45 years and > 45 years) was studied using the bioinformatics method (UALCAN database), immunohistochemical method, and real-time PCR. Results: It was established that a characteristic feature of BCa in young patients is the low level of MMP2 mRNA against the background of increased expression of this gelatinase at the protein level, as well as decreased expression of MMP9 at both the mRNA and protein levels. When analyzing the correlation of the gelatinase expression indices in BCa tissue of young patients, depending on the clinical and pathological features, a significantly lower level of MMP-2 expression was recorded in BCa cases of stage II compared to the indices of stage I cases. High expression of MMP-2 and -9 was recorded in BCa tissue in node-positive cases and the basal molecular BCa subtype. Conclusions: The identified relationship between the expression of the studied gelatinases and such indices of BCa malignancy as its stage, positive regional lymph node status, and the molecular BCa subtype in young patients indicates the need for further research of the features of the tumor microenvironment to predict the cancer aggressiveness.